Highly efficient generation of mature megakaryocytes and functional platelets from human embryonic stem cells - Chuxin Chen; Ning Wang; Xueyan Zhang; Yingjie Fu; Zhiyong Zhong; Haibin Wu; Yaming Wei; Yuyou Duan (Stem Cell Research & Therapy)
Abstract Background Platelet transfusion therapy has made a great breakthrough in clinical practice, and the differentiation of human embryonic stem cells (hESCs) to produce functional platelets has become a new potential approach, however, efficient generation of functional platelets still faces great challenges. Here, we presented a novel approach to highly and efficiently generate mature megakaryocytes (MKs) and functional platelets from hESCs. Methods In hypoxic conditions, we successfully replicated the maturation process of MKs and platelets in a controlled in vitro environment by introducing an optimal combination of cytokines at various stages of development. This method led to the generation of MKs and platelets derived from hESCs. Subsequently, mature MKs and functional platelets were further comprehensively investigated and characterized using a variety of methodologies, including flow cytometry analysis, RT-qPCR validation, Giemsa-Wright’s staining, immunofluorescent staining, RNA transcriptome analysis, and DNA ploidy analysis. Additionally, the in vivo function of platelets was evaluated through the transplantation using thrombocytopenia model mice. Results Under our 3D differentiation conditions with four sequential stages, hESCs could be efficiently induced into mature MKs, with 95% expressing CD41aCD42a or 90% expressing CD41aCD42b, and those MKs exhibited polyploid properties, produced filamentous proplatelet structures and further generated platelets. Furthermore, 95% of platelets showed CD42b+CD62p+ phenotype upon the stimulation with ADP and TRAP-6, while 50% of platelets exhibited the ability to bind PAC-1, indicating that hESC-derived platelets possessed the in vitro functionality. In mice models of thrombocytopenia, hESC-derived platelets effectively restored hemostasis in a manner comparable to human blood-derived platelets. Further investigation on the mechanism of this sequential differentiation revealed that cellular differentiation and molecular interactions during the generation of hESC-derived MKs and platelets recapitulated the developmental trajectory of the megakaryopoiesis and thrombopoiesis. Conclusions Thus, our results demonstrated that we successfully established a highly efficient differentiation of hESCs into mature MKs and functional platelets in vitro. The in vivo functionality of hESC-derived platelets closely resembles that of natural human platelets, thus offering a promising avenue for the development of functional platelets suitable for future clinical applications.